Speech Acts and Principles of Daily in Dental Post Advertisements on Youtube Period (2015-2018) - Ni Putu Andini Desiyanti Laksmi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
Every utterance that is uttered has a certain purpose and meaning. Thus, an effort is needed to interpret the utterance which is called speech acts. The aims of this research is to explain (1) types of speech acts (2) categories of illocutionary acts, and (3) politeness principles contained in the utterance on toothpaste advertisements on youtube period (2015-2018). The data in this research were taken from toothpaste advertisements that have been shown on television channels. The data collected are in the form of image footage and utterances contained in the advertisement. The results of the analysis show that (1) there is a difference between locution and illocutionary acts in adult’s and children's toothpaste advertisements, namely that adult toothpaste advertisements highlight information about the advantages of toothpaste, while the children's toothpaste advertisement emphasizes information about nonverbal advertising, (2) illocutionary acts in the advertisement indicated that there were 6 assertive utterances, 9 directive utterances, 6 commissive utterances, 6 expressive utterances, and 2 declarative utterances, (3) the politeness principles found in those advertisements are 15 tact maxims, 4 approbation maxims, and 6 symphaty maxims.